Influence of Big Brother Naija Reality Television Show on the Social Behaviour of Mass Communication Undergraduates of Selected Universities in the North Central, Nigeria - Adepeju, Adenekan Sofiat; Rabiu, Muhammad S.; Ugande, Anthony (Darul Yasin Al Sys, 2025)
This study investigates the influence of the Big Brother Naija (BBN) reality television show on the social behaviour of mass communication undergraduates at Bingham University, Karu, and the University of Abuja in Nigeria’s North Central region. The objectives were to assess students’ level of exposure to BBN and to examine how the show shapes their social behaviour. The research was grounded in the Uses and Gratification Theory and Cultivation Theory, and employed a survey method using questionnaires administered to a convenience sample drawn from a combined student population of 5,123 (1,900 from Bingham University and 3,223 from the University of Abuja). Findings reveal a high level of exposure to BBN among the respondents, indicating active engagement and widespread viewership. However, students consistently reported that the show lacks cultural enrichment, viewing it as failing to contribute positively to cultural values and norms. The study concludes that although BBN commands strong viewership, its perceived cultural impact is limited, and it recommends that television program producers and regulatory bodies reconsider content strategies to enhance cultural relevance. By highlighting the tension between audience engagement and cultural value, this research provides a foundation for future studies on the relationship between reality television, cultural norms, and social behaviour.